2023
DOI: 10.3390/children10071266
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes around First Aid and Basic Life Support of Kindergarten and Elementary School Teachers and Parents in Taif City, Saudi Arabia

Shadi Tamur,
Raghad Mousa Alasmari,
Matooqa Abdulkareem Alnemari
et al.

Abstract: Background: The foremost cause of children’s (1–19 year) death is inadvertent injuries. While most of these accidental harms occur at home and school, rapid and suitable parental and teacher intervention is required to increase the chances of a child’s survival. Therefore, both parents and teachers of the children in kindergarten and elementary school must be knowledgeable in first aid practice and basic life support (BLS) training. Objectives: In the current study, our ambition is to evaluate the orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This has the potential of changing the current poor trend in the number of Nigerian bystander CPR-untrained athletes, as well as in other African countries. In a recent related study [41], 21.9% of the participants (teachers and parents) claimed to have had previous bystander CPR trainings but most of them were supposed to have gone for re-training after two years of initial trainings. They concluded that a sizable portion of the contributors expressed a lack of proficiency in the fundamental CPR training knowledge and skills, pointing to an alarming public concern in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential of changing the current poor trend in the number of Nigerian bystander CPR-untrained athletes, as well as in other African countries. In a recent related study [41], 21.9% of the participants (teachers and parents) claimed to have had previous bystander CPR trainings but most of them were supposed to have gone for re-training after two years of initial trainings. They concluded that a sizable portion of the contributors expressed a lack of proficiency in the fundamental CPR training knowledge and skills, pointing to an alarming public concern in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Tamur et al, it was found that the majority of those involved in the study did not have an understanding of CPR training [15]. However, they were willing to learn.…”
Section: Discussionmentioning
confidence: 99%